Hobbes on resistance : defying the Leviathan - Sreedhar, Susanne (Cambridge University Press, 2010)
"Hobbes's political theory has traditionally been taken to be an endorsement of state power and a prescription for unconditional obedience to the sovereign's will. In this book, Susanne Sreedhar develops a novel interpretation of Hobbes's theory of political obligation and explores important cases where Hobbes claims that subjects have a right to disobey and resist state power, even when their lives are not directly threatened. Drawing attention to this broader set of rights, her comprehensive analysis of Hobbes's account of political disobedience reveals a unified and coherent theory of resistance that has previously gone unnoticed and undefended. Her book will appeal to all who are interested in the nature and limits of political authority, the right of self-defense, the right of revolution, and the modern origins of these issues"--